การศึกษาพัฒนาการของระบบสื่อสารมวลชนในสาธารณรัฐประชาธิปไตยประชาชนลาว ค.ศ.1950-1997 - ทองปาน สมพะวง (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This qualitative research was aimed at understanding of development, factor affecting mass media system in Lao during AD. 1950-1997 and trend of Lao s media system in the future. Systems Theory, Organization Theory, Authoritarian Theory, Soviet-Communist Theory and Communication Development Theory were applied as a conceptual framework of this study. Results indicated that Lao s media system was originated from the political leaders in each period who called for the media which had the development as follows: In first phase, Lao s media system had two formats in the same country as Kingdom of Lao had 13 newspapers, 8 radio stations and 15 cinemas and Country of Lao had 3 newspapers and 2 radio stations. In second phase, Lao s media system had only one system which was govemment media system to serve the indeology of government in reforming the country. There were 8 newspapers, 6 radio stations, 6 cinemas and one television station. In third phase, Lao s media system was under government control which aimed at motivating economic and social development. There were 11 newspapers, 27 journals, 15 radio stations and 17 television stations. Lao s media system strongly congregated which each media was under government organizations controls and/or the role of Lao s relations in each period. Factors affecting media system were economy, politics, society and technology. Politics factor determined the changing of media system. In the future, the trend of Lao s media system is that it will develop according to the change of economy, politics and technology and the influence of transnational corporations will increase which contents will be variety and will be better and faster in satisfyin gpeoples needs.